Criterion validity and reliability of the International Physical Activity Questionnaire - Hungarian short form against the RM42 accelerometer - Pongrác Ács; Réka Veress; Paulo Rocha; Tamás Dóczi; Bence László Raposa; Petra Baumann; Sergej Ostojic; Viktória Pérmusz; Alexandra Makai (BMC, 2021)
Abstract Background Physical inactivity is a global phenomenon in European welfare countries. Proper monitoring is essential to measure the physical activity level of the population. Methods In the Hungarian cohort of the European Physical Activity and Sport Monitoring System (EUPASMOS) project, our participants (N = 598) completed sociodemographic questions and the International Physical Activity Questionnaire - short form (IPAQ-SF) survey. The validity and reliability of the subjective measurement tool were examined, IPAQ-SF outcomes were contrasted against triaxial RM42 accelerometer wore for 7 consecutive days. Results The IPAQ-SF showed moderate internal consistency (Cronbach Alpha = 0.647). The concurrent validity of the IPAQ-SF to triaxial accelerometer indicated a significant weak-to-moderate correlation (R = 0.111-0.338, p = 0.042; p < 0.001). The test-retest reliability showed a significant correlation between two measurements (R = 0.788-0.981, p < 0.001). Conclusion The Hungarian version of the IPAQ-SF had excellent test-retest reliability, but low-to-fair concurrent validity for moderate and vigorous physical activity, walking and sitting time, as compared to the objective criterion measure among Hungarian adults.